Analysis of Public Policy in Overcoming the Poverty Phenomenon in Indonesia - Budiansyah Budiansyah (SEAN Institute, 2023)
The purpose of this research is to find out how the public policies made by the Indonesian government overcome the existing poverty phenomenon. Poverty is one of the fundamental problems that arises in every country, especially in Indonesia. The problem of poverty seems to be very urgent to be addressed by various parties. In plain view, the condition of poor people can be seen from those who cannot fulfill basic needs, have limited sources of income, do not have basic facilities and infrastructure, such as adequate housing, the quality of the environment is slum and uninhabitable. This research uses descriptive analysis as a research method, using a qualitative approach and the research results explain that poverty is one of the fundamental problems that is the center of attention of all parties. Until now, the Central Government and Regional Governments are still facing complex and multidimensional poverty problems. The difficulty of solving the problem of poverty is because poverty is a complex problem related to various dimensions, including social dimensions, cultural dimensions and even structural dimensions. The problem of poverty is emphasized more on the quality of life and income distribution. Poverty is a problem that requires overcoming and a systematic, integrated and comprehensive approach to meet the burden and fulfill the basic rights of citizens through inclusive, just and sustainable development to achieve a dignified life.